Estimation of Ketorolactromithamine in Phamaceutical Samples and Biofluids by The New Validated UPLC Method - Mohammad Nasir Uddin; Monir Uddin; Md. Touhidul Kabir; Suman Das (Chemistry Department, The University of Brawijaya, 2017)
A new UPLC method has been described to determine ketorolac tromethamine in pharmaceutical samples and biofluids. Drug was eluted using a reversed-phase Gemini 3U, C18, 110R (150 × 4.6 mm, 3 μm) column when a mobile phase composition 90:05:05 (v/v) consisting CH3OH, CH3CN and NaH2PO4 under isocratic program.Ketorolac tromethamine was eluted at a short of time 2.02 min. Ketorolac tromethamine isolated from biofluids after liquid-phase extraction. The results were linear up to 10 µg mL-1 with the correlation coefficients greater than 0.999. The sensitivity limits, LOD and LOQ were 0.016 and 0.051 µg mL-1, respectively. The method is simple, fast and reliable with good specificity and sensitivity and will be suitable for routine analysis of ketorolac tromethamine.